Information System for Monitoring Waste Tonnage and Fleet Assignment at the Medan City Sanitary and Park Agency - Ahmad Hisdan; M.Fakhriza (Jurnal Info Sains : Informatika dan Sains, 2023)
The Medan City Sanitary and Parks Department has the responsibility of carrying out the waste transportation process from the source of waste to the location of the Sanitary Landfill. Every day, the waste transportation vehicle receives a Road Order Letter from the sub-agency located in the sub-district, which contains information on waste transportation information. After the transportation is complete, the letter is submitted to the landfill scale department for tonnage and origin data collection. However, at present, all waste transportation data collection activities are carried out manually, including the provision of assignment letters and data collection of waste tonnage and fleet routes at the landfill. This results in ineffectiveness in the data collection operations. This encourages researchers to design a monitoring and fleet assignment information system at the Medan City Sanitary and Parks Service. Data collection is done by observation and interviews. The system development model in this system uses SDLC (System Development Life Cycle) Waterfall and uses UML (Unified Modeling Language) as a method of describing the flow of the system by applying the Use Case Diagram, Activity Diagram and Sequence Diagram models. The system is designed to run on a website system and is built using the PHP programming language with MySQL as a database. With this system, it is hoped that it can help in facilitating fleet assignments and monitoring the amount of waste entering the Sanitary Landfill .